Literary and Philosophical Background of the Playwright Ibsen: Revisited - Lubna Marqus Khoshaba; Misbah M.D. Al-Sulaimaan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
A literary text is a mirror that reflects the author’s life, feelings, emotions, and sufferings. To understand the literary work, one should take into consideration two main aspects: literary and philosophical. The literary aspect includes the style used by the author, and literary devices implemented in his writings such as metaphor, irony, pun and so on. As for the philosophical aspect, it shows different schools to which the author is affected by whether it is realism, naturalism or any other approach. The current study consists of five sections: (1) an introduction about Ibsen, (2) literary background of Ibsen which includes his style and main literary devices, (3) philosophical background of Ibsen which includes the philosophical schools that are reflected in his plays, (4) context and its role in understanding and analyzing Ibsen’s work, and (5) the main conclusion that the study came up with is that context plays a great role in understanding the phenomenon under discussion.